A CFD study and geometrical improvement on heavy duty diesel engine for ultra-low emissions - (:unkn) unknown (My University, 2010)
The goal of this study is to find out effects of the injection parameters on the combustion process for a single cylinder of a nine-liter six cylinder diesel engine. Partially premixed compression ignition (PPCI) cases are compared for improvements on the combustion chamber design of the engine to achieve near zero particulate matter (PM) and NOx emissions for homogenous charge compression ignition (HCCI) engine. Therefore combustion simulations of the engine have been performed to find out flow development and emission generation in the cylinder. Moreover, the interaction of air motion with high-pressure fuel spray injected directly into the cylinder has also been analyzed. Finally, a comparison has been made considering the performance of the engine for various configurations such as compression ratio, injection timing, cone angle and bowl geometry. The results are widely in agreement qualitatively with the previous similar experimental and computational studies in the literature. Copyright © 2010 by ASME.
Keywords: CFD; Clean diesel combustion; Combustion; Combustion chamber; Emissions; Injection parameters; Narrow angle; Spray